Creativity and Its Discontents : China's Creative Industries and Intellectual Property Rights Offenses - Pang, Laikwan; Project Muse. (Durham [N.C.] : Duke University Press, 2012)
Laikwan Pang offers a complex critical analysis of creativity, creative industries, and the impact of Western copyright laws on creativity in China.
Creativity as a problem of modernity -- Creativity as a product of labor -- Creativity as a construct of rights -- Cultural policy, intellectual property rights, and cultural tourism -- Cinema as a creative industry -- Branding the creative city with fine arts -- Animation and transcultural signification -- A semiotics of the counterfeit product -- Imitation or appropriation arts?
English.
Description based on print version record.
Keywords: Law and economic development; Intellectual property infringement; Intellectual property; Cultural industries; Creative ability -- Economic aspects; ART -- Business Aspects; Copyright law; Droit et developpement; Infractions à la propriete intellectuelle -- Chine; Propriete intellectuelle -- Chine; Creativite -- Aspect economique -- Chine; Industries culturelles -- Chine; Law and economic development; Intellectual property infringement -- China; Intellectual property -- China; Creative ability -- Economic aspects -- China; Cultural industries -- China; China; Electronic books